SKRINING FITOKIMIA DAN BIOAKTIVITAS RHODOMYRTUS TOMENTOSA (AITON) HASSK) (KARAMUNTING) - Erwin, Erwin; Ilham, Muhammad Hafid; Pratiwi, Djihan Ryn; Alimuddin, Alimuddin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Rhodomyrtus tomentosa (Aiton) Hassk) or known as Karamunting, is one of the medicinal plants. This medicinal plant is used by the community as a medicine for colic, fever, dysentery, sepsis, to treat shortness of breath or pain, tuberculosis, abscesses, bleeding and gynecopathy. In this study, phytochemical and bioactivity tests will be carried out on Rhodomyrtus tomentosa leaves, stem and bark extracts. Research methods include maceration of the sample with methanol, separation of the filtrate solvent obtained from the extract using a rotary evaporator, determination of chemical content using a phytochemical test, and determination of bioactivity using the brine shrimp lethality test (BSLT) method. Based on the results of phytochemical tests, it was found that the leaf extract contained alkaloids, steroids, phenolics, flavonoids, saponins and quinones. Stem extract contains alkaloids, phenolics, flavonoids, saponins and quinones. and stem bark extract contains triterpenoids, phenolics, saponins and quinones. Meanwhile, the results of the bioactivity test showed that only the leaf extract was toxic to Artemia salina shrimp with an LC50 of 582.10 ppm, while the leaf and stem bark extracts were inactive with an LC50 value above 1000 ppm. Keywords: Karamunting, BSLT test, phytochemical test, and Artemia Salina L